Postpartum Ovarian Activity In Sahiwal- Friesian Cows Fed Different Levels Of Energy - Haji Mohd Adam, Azillah (1984)
Postpartum ovarian function was determined by milk progesterone radio immunoassay in 21 first - calf Sahiwal-Friesian cows assigned to one of three treatment groups designated as low , medium an d high energy level sen=7 ) . The progesterone concentrations in defatted milk were determined thrice weekly for 120 days postpartum. Mean interval to resumption of ovarian activity and t o forst ovulation was longest in the low energy group and short - est in t he high energy group . Using progesterone concentration of>1ng/ml as criteria for corpus luteum activity , first ovulation occurred at 37.7 ± 18.0,26.6 ±15.7 and 25.3 ± 8.4 days for low , medium and high energy groups , respectively. However , first estrus was observed at 28.0 ± 21.6,32.7+ 9.8 and 25.4+ 6.0 days , respectively.The percentages of silent estrus were 13.6 percent , 29.6 percent and 14.3 percent for low , medium and high energy groups , respectively , with a majority ( 46.7 percent ) detected during the initial postpartum estrous cycle .